THE STRUCTURAL-FUNCTIONALISM THEORY AND DUAN-LOLAT RELATIONSHIP IN TANIMBAR, MOLUCCAS-INDONESIA - Masriat, Cayetanus (Fides et Ratio : Jurnal Teologi Kontekstual Seminari Tinggi St. Fransiskus Xaverius Ambon, 2017)
One of the systems of relations within Tanimbar society (in Moluccas, Indonesia), that is surviving until today is the relation of the duan and lolat. This relation system greatly affects the life of Tanimbar community. In many of the events of life, especially with regard to the life cycle of Tanimbar people, the relation between duan and lolat is always placed as an important factor. Because it is considered as on the most important kind of relationship, West- Southeast Moluccas Regency Government takes the duan and lolat as the symbol of West- Southeast Moluccas Regency.